2020
DOI: 10.1021/acs.jpcb.0c06795
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Sedimentation Velocities and Equilibria in Dilute Aqueous Ferrofluids

Abstract: Dilute ferrofluids have important applications in the separation of materials via magnetic levitation. However, dilute ferrofluids pose an additional challenge compared to concentrated ones. Migration of the magnetic nanoparticles toward a magnet is not well counteracted by a buildup of an osmotic pressure gradient, and consequently, homogeneity of the fluid is gradually lost. Here, we investigate this phenomenon by measuring and numerically modeling time-dependent concentration profiles in aqueous ferrofluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The synthesis of magnetite nanoparticles by chemical co-precipitation is a scalable and cost-effective procedure as it does not need or produce toxic intermediates, and does not require precursor complexes and it proceeds at moderate temperatures below 100 °C. 76–78…”
Section: Synthesis Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis of magnetite nanoparticles by chemical co-precipitation is a scalable and cost-effective procedure as it does not need or produce toxic intermediates, and does not require precursor complexes and it proceeds at moderate temperatures below 100 °C. 76–78…”
Section: Synthesis Proceduresmentioning
confidence: 99%
“…75 The synthesis of magnetite nanoparticles by chemical coprecipitation is a scalable and cost-effective procedure as it does not need or produce toxic intermediates, and does not require precursor complexes and it proceeds at moderate temperatures below 100 °C. [76][77][78] An interesting type of multicore magnetic nanoparticle is nanoflowers, the assembly of monocrystalline grains to be used as the magnetoresponsive component of a bio-ferrofluid. Nanoflowers have an exceptional hyperthermic efficacy, and their specific loss power (SLP) is one order of magnitude higher than that reported for the single core MNPs of the same size under the same AC field exposure, so they have shown outstanding interest since their first discovery.…”
Section: Synthesis Of Magnetic Nanoparticles For Ferrofluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetically active particles in these fluids are so small that they are not subject to sedimentation effects, allowing them to remain suspended due to Brownian motion. Ferrofluids can therefore be used for applications where a continuous and homogeneous phase is mandatory [20]. Kurto glu et al clearly showed that a homogenous system of magnetically active nanoparticles can be used for this purpose [21].…”
Section: Introductionmentioning
confidence: 99%